Taiwan's threatened democracy stays on course: Fear of China's dictatorship pushes Taiwan's president to a landslide victory - Frédéric Krumbein (Stiftung Wissenschaft und Politik (SWP), 2020)
Presidential and parliamentary elections were held in Taiwan on 11 January 2020. The island is de facto a sovereign state and a consolidated democracy but is claimed by the People's Republic of China. Taiwan's president, Tsai Ing-wen, who has been in power since 2016, and her Democratic Progress Party (DPP) won both elections by a clear majority. The DPP stresses Taiwan's de facto independence. The largest opposition party, Kuomintang (KMT), stands for closer economic cooperation with mainland China. The election campaign was marked by increasing pressure from Beijing on the island and by protests in Hong Kong. Hong Kong serves as a warning to the Taiwanese about what could happen if Taiwan becomes too close to the mainland or even merges with it: The island state could lose its democracy and freedom.
Keywords: 320